Thermo-economic optimization of a hybrid solar district heating plant with flat plate collectors and parabolic trough collectors in series. (1st June 2018) - Tian, Zhiyong; Perers, Bengt; Furbo, Simon; Fan, Jianhua
Highlights: A generic multivariable thermal-economic optimization approach was developed. The influences of different aim functions on the varied optimal results were shown. Sensitivity analysis of the key design parameters was carried out. The optimal heat price could provide practical reference for the end-use consumers. The system levelized cost of heat can be reduced by 5–9% in this study. Abstract: Large-scale solar heating plants for district heating networks have gained great success in Europe, particularly in Denmark. A hybrid solar district heating plant with 5960 m 2 flat plate collectors and 4039 m 2 parabolic trough collectors in series was built in Taars, Denmark in 2015. The solar heating plant was used as a reference case in this study. A validated TRNSYS-GenOpt model was set up to optimize the key design parameters of the plant, including areas of both collector types, storage size, orientation of the parabolic trough collectors and so on. This study introduces a generic method to optimize the hybrid solar district heating systems based on levelized cost of heat. It is found that the lowest net levelized cost of heat of hybrid solar heating plants could reach about 0.36 DKK/kWh. The system levelized cost of heat can be reduced by 5–9% by use of solar collectors in the district heating network in this study. The results also show that parabolic trough collectors are economically feasible for district heating networks in Denmark. The generic and multivariable levelized cost of heat method can guide engineers and designers on the design, construction and control of large-scale solar heating plants.